Project activity as a means of the formation of professional competence of future teachers (Pedagogy of Higher and Secondary Education, 2012)
Breslavskaya A. Project activity as a means of the formation of professional competence of future teachers.The article deals with the problem of project activity as a means of the formation of professional competence of future teachers. The author shows the possibilities of the project method for students’ professional training.
Keywords: project; project activity; professional competence